An Investigation of the Types of Power Used by High School Teachers in Classroom Management According to Teachers' and Students' Opinions - Sadık Fatma; Nasırcı Hasan (Sciendo, 2022)
Introduction: Power relationships, which manifest themselves in all kinds of organizational environments, including educational institutions, manifest themselves as a necessity for teacher leadership in the classroom. It is necessary to use different types of power, which are multi-sourced and influenced by more than one variable, in classroom management to increase the quality of education. Due to these reasons, this study aimed to comparatively examine the types of power used by high school teachers in classroom management according to the opinions of teachers and students.